Ultrasound and Thermosonication as Promising Technologies for Processing Plant-Based Beverages: A Review - Dalia M. Sotelo-Lara; Genaro G. Amador-Espejo; Diego F. Álvarez-Araiza; Alondra K. Cordero-Rivera; Karla G. Millán-Quintero; Rocío Campos-Vega; Rita M. Velázquez-Estrada (Food Technology and Biotechnology)
Plant-based beverages are water-soluble extracts of cereals, pseudocereals, seeds and legumes that resemble milk in appearance. However, these products have important differences compared to normal liquid milk, such as nutritional composition, sensorial properties and shelf-life stability. Increasing number of consumers are opting for these beverages due to lactose intolerance, milk protein allergies or lifestyle. In this regard, different emerging technologies have been investigated to solve problems such as shelf life, nutritional and emulsion stability as well as sensory acceptability, without using high temperatures since heat treatments decrease the content of some bioactive compounds. Ultrasound technology alone or combined with temperature (thermosonication) could be a valuable tool to improve the properties of plant-based beverages. Therefore, this review provides a detailed analysis of the effect of ultrasound and thermosonication on the physical, bioactive, microbiological and sensory properties of almond-, soybean-, coconut-, hazelnut- and peanut-based beverages, among others.